ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA PT UNIVERSAL CARD INDONESIAN JAKARTA - Yulita Sari; Triyadi (PT. Hasba Edukasi Mandiri, 2025)
This research aims to analyze effective marketing strategies in increasing sales of PT Universal Card Indonesia in the hotel industry. Key cards are a critical tool in hotel operations, and increasing sales can impact operational efficiency and customer satisfaction. This research uses a qualitative method with a case study approach on several hotels that have succeeded in increasing their sales through appropriate marketing strategies. Based on the results of the analysis, the marketing strategy was carried out using SWOT analysis. Apart from that, implementing a more personalized marketing strategy at PT Universal Card Indonesia. And the research instruments used are observation, interviews, documentation and the researchers themselves. This research concludes that by implementing the right marketing strategy, key card sales can increase significantly, which in turn can increase revenue and customer loyalty.